Recruit to Retain: Recruitment Challenges in Emerging Economy || Focus on Large Corporations in IT Sector - Joseph, Michael A. (Digital Repository of Theses - SSBM Geneva, 2025)
The rapid evolution of the IT industry presents ongoing challenges in recruitment and workforce retention, necessitating strategic adaptations to both external and internal influences. This study examines the key factors shaping IT recruitment, including economic conditions, industry demand, technological advancements, government regulations, and shifting employee expectations. It further explores how organizations balance these external constraints with internal workforce strategies such as upskilling, career development, and flexible work arrangements to enhance talent acquisition and retention. Utilizing a mixed-methods approach, the research incorporates quantitative surveys, literature reviews to assess recruitment and retention patterns across large IT organizational structures. The findings reveal that while economic stability and industry growth drive recruitment activity, talent shortages remain a persistent concern due to changing skill demands. Organizations facing strict immigration policies or local talent scarcity increasingly rely on alternative hiring strategies, including tapping remote work models, gig workforce and international outsourcing. Moreover, AI-driven hiring tools improve efficiency but are unable to replace human intelligence, Insights and experience to ensure effective selection and retention of top talent in organizations. The study also identifies key retention drivers, emphasizing the importance of employer branding, mentorship programs, structured career progression, and competitive benefits. Findings indicate that generational differences influence employee satisfaction, with younger professionals prioritizing career growth and workplace culture, while experienced employees value stability and leadership opportunities. Additionally, organizations with strong leadership transparency and employee recognition programs report lower attrition rates. A critical contribution of this research is the development of a framework integrating external and internal factors to optimize IT workforce management. The results suggest that addressing IT talent shortages requires a dual focus—enhancing both recruitment efficiency and retention strategies. Organizations that foster a supportive work environment, implement structured development programs, and align hiring policies with workforce expectations can achieve sustainable workforce stability. This study provides valuable insights for HR professionals, IT managers, and policymakers aiming to improve recruitment outcomes and long-term workforce retention. Future research should explore the long-term impact of hybrid work models, AI integration in hiring, and evolving workforce expectations in the digital economy. Keywords: IT recruitment, workforce retention, talent shortages, AI-driven hiring, employee engagement, career development, workforce planning.